BIO MECHANICS OF THE KNEE - Gülcan Gürer; Bülent Seçkin (Archives of Rheumatology, 2001)
The biomechanics of the knee joint should be learned well in order to understand the pathogenesis of the diseases of the bissest joints of the body. In this article anatomy and the functions of the knee joint and the stresses which play a role on the knee joint was discussed briefly.